HOXA5 Participates in Brown Adipose Tissue and Epaxial Skeletal Muscle Patterning and in Brown Adipocyte Differentiation - Holzman, Miriam A.; Ryckman, Abigail; Finkelstein, Tova M.; Landry-Truchon, Kim; Schindler, Kyra A.; Bergmann, Jenna M.; Jeannotte, Lucie; Mansfield, Jennifer H. (Frontiers in Cell and Developmental Biology, 2021)
Brown adipose tissue (BAT) plays critical thermogenic, metabolic and endocrine roles in mammals, and aberrant BAT function is associated with metabolic disorders including obesity and diabetes. The major BAT depots are clustered at the neck and forelimb levels, and arise largely within the dermomyotome of somites, from a common progenitor with skeletal muscle. However, many aspects of BAT embryonic development are not well understood. Hoxa5 patterns other tissues at the cervical and brachial levels, including skeletal, neural and respiratory structures. Here, we show that Hoxa5 also positively regulates BAT development, while negatively regulating formation of epaxial skeletal muscle. HOXA5 protein is expressed in embryonic preadipocytes and adipocytes as early as embryonic day 12.5. Hoxa5 null mutant embryos and rare, surviving adults show subtly reduced iBAT and sBAT formation, as well as aberrant marker expression, lower adipocyte density and altered lipid droplet morphology. Conversely, the epaxial muscles that arise from a common dermomyotome progenitor are expanded in Hoxa5 mutants. Conditional deletion of Hoxa5 with Myf5/Cre can reproduce both BAT and epaxial muscle phenotypes, indicating that HOXA5 is necessary within Myf5-positive dermomyotome cells for proper BAT and epaxial muscle development. However, recombinase-based lineage tracing shows that Hoxa5 does not act cell-autonomously to repress skeletal muscle fate. Interestingly, Hoxa5-dependent regulation of adipose-associated transcripts is conserved in lung and diaphragm, suggesting a shared molecular role for Hoxa5 in multiple tissues. Together, these findings establish a role for Hoxa5 in embryonic BAT development.